Implementation of Big Data and Technology in Improving The Quality of Auditor's Audit Results (Case Study at BPK The Riau Province) - Ariyanto, Sanusi (Jurnal Riset Akuntansi dan Auditing, 2024)
This study aimed to determine the effects of data science implementation and examiner performance technology at the government auditor's office. The variables were data science and technology, and the performance of financial examiners as a dependent variable during the pandemic. A descriptive method in the form of correlation studies with a quantitative approach was used to determine the effect. It is expected that more accurate measurement results about the responses given by respondents would be obtained so that data in the form of numbers could be processed using statistics, namely normality tests, tests of validity, reliability, and hypothesis testing. This study's population was confined to the financial examiners of the government auditor office, with the sample consisting of 43 auditors. A google form questionnaire with a likert scale was used for sampling. The data were analyzed at a 95% significance level. Regression analysis was employed as an analytical tool in this study. The novelty of this research is how the use of big data and technology has a vital role in auditing, especially remote audits because it does not allow for field inspections during the pandemic. Result of this study, the big data and technology variables had a beneficial impact on the quality of government auditors during the pandemic period. Abstrak - Tujuan dari penelitian ini adalah untuk mengetahui pengaruh implementasi ilmu data dan teknologi kinerja pemeriksa pada kantor auditor pemerintah. Variabel penelitiannya meliputi variabel independen seperti data science dan teknologi, serta variabel dependen yaitu kinerja pemeriksa keuangan pada masa pandemi. Untuk mengetahui pengaruhnya digunakan metode deskriptif berupa studi korelasional dengan pendekatan kuantitatif. Diharapkan diperoleh hasil pengukuran yang lebih akurat terhadap tanggapan yang diberikan responden, sehingga data yang berupa angka-angka dapat diolah dengan menggunakan statistik yaitu uji normalitas, uji validitas, reliabilitas, dan uji hipotesis. Populasi penelitian ini dibatasi pada pemeriksa keuangan pada kantor auditor pemerintah. Sampel penelitian penelitian ini terdiri dari 43 auditor. Kuesioner formulir google dengan skala likert digunakan untuk pengambilan sampel. Data dianalisis pada tingkat signifikansi 95%. Analisis regresi digunakan sebagai alat analisis dalam penelitian ini. Kebaruan dari penelitian ini adalah bagaimana penggunaan big data dan teknologi memiliki peran yang sangat vital dalam audit, terutama penggunaan audit jarak jauh karena tidak memungkinkan dilakukannya inspeksi lapangan di masa pandemi. Hasil penelitian variabel data dan teknologi memberikan dampak positif terhadap kualitas auditor pemerintah pada masa pandemic.